Vriesea mourae (Bromeliaceae), a new critically endangered species from Serra da Bocaina, southeastern Brazil - Kessous, Igor M.; Neves, Beatriz; Costa, Andrea F. (Phytotaxa, 2018)
A new, critically endangered taxon, Vriesea mourae, endemic to the Serra da Bocaina mountains in southeastern Brazil, is described. We provide data on its conservation status, etymological and taxonomic notes, photographs, and illustrations. The taxon is morphologically similar to V. warmingii, differing mainly in the shorter blade, diameter of peduncle and rachis, inflorescence length, floral bract shape and color, sepal shape, petal shape, length, and color.